Perbandingan Dampak Psikologis Konflik Bersenjata Populasi Urban vs Rural di Yaman : Suatu Systematic Review - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (Lembaga Pengembangan Kinerja Dosen, 2025)
This study analyzes the psychological impact of the armed conflict in Yemen by comparing urban and rural populations through a systematic review and meta-analysis of 47 published studies (N=28,463) from 2015 to 2024. The analysis reveals a significantly higher prevalence of PTSD in the urban population (42.8%, 95% CI [39.2-46.4]) compared to the rural population (31.5%, 95% CI [28.1-34.9], p<.001). In addition, multilevel regression analysis indicates a strong correlation between the level of exposure to conflict and the severity of depressive symptoms (r=.68, p<.001) and anxiety (r=.72, p<.001) in both populations. Additionally, when examining specific urban risk factors, calculations indicate that population density (OR=1.86, 95% CI [1.54-2.18]) and loss of infrastructure (OR=1.73, 95% CI [1.45-2.01]) are significant. Moreover, geographic isolation (OR=1.92, 95% CI [1.67-2.17]) and limited access to mental health services (OR=2.14, 95% CI [1.89-2.39]) also demonstrate prominent risk factors, thereby emphasizing the predominance of specific urban risk factors in rural areas. These findings contrast with the research conducted by Le & Nguyen (2023) and Carpiniello (2023), which focused solely on general impacts; thus, the novelty of this research lies in its success in identifying distinct patterns of psychological trauma based on geographic characteristics. In addition, this study successfully reveals the differing mediating mechanisms of social support between urban (β=-.42, p<.001) and rural (β=-.28, p<.01) populations in mitigating the impacts of the Yemeni war trauma.